Semantic meaning of the lexeme «红/ red» in Chinese and Russian (Proceedings of Southern Federal University. Philology, 2015)
The article studies the semantic meaning of the lexeme "红 / red" in Chinese and Russian. It is considered in detail red color in Chinese and Russian languages, offered authoritative Chinese and Russian lexicographic dictionaries. It is carried out a comparative analysis of the meaning of the lexeme "IX» and "red", it is defined semantic groups of lexemes "红/ red" in Chinese and Russian, it is identified features of similarities and differences. It is concluded that the red color in Chinese and Russian is mostly of positive tone; lexeme "红 / red" in both languages has both similar and characteristic for each language connotations. The semantic meaning of red in Chinese and Russian due to linguacultural features is expressed in the national symbolism of color.Keywords: red, semantic meaning, Chinese, Russian.Denisova Valeria Lvovna - Post-graduate student of Huazhong University of Science and Technology (Hubei, Wuhan, China). Chinese Philology. Department of Chinese language and Literature. School of Humanities. Tel.: +7 (4212) 48-77-29; e-mail: I201322167@hust.edu.cn